Effect of drought on morphological and functional traits of Poa ligularis and Pappostipa speciosa, native perennial grasses with wide distribution in Patagonian rangelands, Argentina - Cenzano, Ana María (2013)
Poa ligularis Nees. Ap. Steudel and Pappostipa speciosa (Trin. et Rupr.) Romaschenko are dominant perennial grasses in the arid Patagonian rangelands of Argentina. Both species are exposed to periods of water shortage during spring-summer and are grazed by domestic and native herbivores. Pappostipa speciosa displays xeromorphic adaptations and is less preferred by herbivores than P. ligularis. The knowledge of how drought affects morphological/functional traits in coexisting perennial grass species is useful to understanding the function of desert perennial grasses, and for the use and conservation of Patagonian arid rangelands. The hypothesis of this study was that co-existing perennial grasses contrasting in drought resistance mechanisms display different degrees of phenotypic plasticity in underlying and/or functional traits. Plants of both species were exposed to two levels of gravimetric soil moisture: 16% (~field capacity) and 4%. Plant vegetative and reproductive traits were measured weekly in individual plants and these were harvested at the end of the experiment. Aboveground and root biomass were separated in the harvested plants and the concentration of photosynthetic pigments was assessed in green leaves. The trait response range was also calculated through the plasticity index. In both species, drought stress led to significant reductions in plant height, total plant dry weight, number of total leaves, dry weight of green and senescent leaf, percentage of flowering plants, length of inflorescences, and number, length and dry weight of roots. The concentration of photosynthetic pigments increased under drought in both species. In conclusion, drought strongly affected reproductive and vegetative traits in both species and the greatest negative effect of drought was found in P. speciosa, the most conservative species. However, our findings might indicate that both species are able to maintain photosynthetic activity through the increase of photosynthetic pigments under drought conditions in Patagonian rangelands.